2017
DOI: 10.3138/jvme.0416-085r
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey of Veterinary Students to Assess Their Use of Online Learning Resources

Abstract: Today's veterinary students have access to a wide range of online resources that support self-directed learning. To develop a benchmark of current global student practice in e-learning, this study measured self-reported access to, and use of, these resources by students internationally. An online survey was designed and promoted via veterinary student mailing lists and international organizations, resulting in 1,070 responses. Analysis of survey data indicated that students now use online resources in a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 28 publications
7
43
0
Order By: Relevance
“…This finding aligns with previously published literature. [7] When students prepared for the course did not impact their academic success but having dedicated time blocked in their schedule was deeply appreciated, especially by students who used the hours to take care of their mental health. A recent survey has shown that around a third of veterinary students participating had clinical levels of depression or anxiety.…”
Section: Learning Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding aligns with previously published literature. [7] When students prepared for the course did not impact their academic success but having dedicated time blocked in their schedule was deeply appreciated, especially by students who used the hours to take care of their mental health. A recent survey has shown that around a third of veterinary students participating had clinical levels of depression or anxiety.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…[6] More than 80% of the veterinary students surveyed by Gledhill et al responded that online quizzes provide a useful opportunity for their self-directed learning. [7] Research also suggests that veterinary instructors believe flipped classroom techniques can encourage students' preparation and self-directed learning in addition to improving students' examination preparation. However, the same instructors also recognize that students' lack of engagement with the material or in class as well as their resistance to this new model of teaching can be strong barriers to the success of the flipped method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One qualitative study reported that upper-year Australian veterinary students’ primary source of stress came from IO [41], although information from the internet was not explicitly mentioned. Given that veterinary students today have ready access to the internet for animal health information [44], similar to their medical counterparts, veterinary students may also be at risk of HIO. Previous research shows that vast volumes of information may be a predisposing factor to HIO for postsecondary students with internet access [45] and potentially for veterinary students who reported searching for content using Google to support their studies [44].…”
Section: Introductionmentioning
confidence: 99%
“…Given that veterinary students today have ready access to the internet for animal health information [44], similar to their medical counterparts, veterinary students may also be at risk of HIO. Previous research shows that vast volumes of information may be a predisposing factor to HIO for postsecondary students with internet access [45] and potentially for veterinary students who reported searching for content using Google to support their studies [44]. Further research indicates that some veterinary students report their training as a chronic stressor [38], which Laakonen and Nevgi [39] suggest may arise from academic demands such as the overwhelming volumes of information students are expected to learn and assimilate.…”
Section: Introductionmentioning
confidence: 99%